Study of Physicochemical Properties of Beeswax Addition to Chocolate Candy Products: Studi Sifat Fisikokimia Penambahan Lilin Lebah Terhadap Produk Permen Cokelat - Arziyah, Dewi; Putri, Aprilia (jurnal makanan tropis dan teknologi agroindustri, 2024)
The development of the cocoa agro-industry in West Sumatra cannot be separated from the variety of products produced including chocolate candy which is the most popular processed cocoa product but this product has the disadvantage of melting easily at room temperature. Beeswax is one of the materials that can be a hardness base that can be applied to food. The use of beeswax in chocolate candy is expected to provide a solution for the cocoa agro-industry. This study aims to determine the effect of different percentages of beeswax on the characteristics of chocolate candy. The design used in this study is a completely randomized design (CRD) with 5 treatments with 3 replications. Observational data were analyzed with variance analysis (ANOVA) if significantly different, DNMRT (Duncan's New Multiple Range Test) was conducted at a real level of 5%. The treatments used were 0%, 5%, 10%, 15%, 20% addition of beeswax percentage to chocolate candy. The results showed that the addition of beeswax percentage had a significant effect on fat, hardness, and organoleptic properties but did not significantly affect the water content of chocolate candy. The physical and chemical values are hardness 209.92 N/cm2, moisture content 1.01%, fat content 44.11%. Meanwhile, the organoleptic test results showed that treatment E was the most desirable product.